Integration of Project-Based Learning in Science, Technology, Engineering, and Mathematics to Improve Students’ Biology Practical Skills in Higher Education: A Systematic Review - Megawati Ruth (Open Education Studies)
Science, technology, engineering, and mathematics (STEM)-integrated project-based learning (PBL) is essential in contemporary education as it improves students’ advanced cognitive capacities, critical thinking aptitude, scientific literacy, and ecological awareness. This study aims to identify and highlight some research publications that examine STEM-integrated PBL to improve students’ biology practical skills in higher education. The author guided the systematic review process with the preferred reporting items for systematic reviews and meta-analyses diagram, ensuring a structured approach to article selection. The author selected 24 potential articles for the literature review based on certain inclusion criteria. The chosen articles emphasize the importance of evaluating STEM-integrated PBL to improve biology practicum skills among students in higher education, highlighting the need for quantitative methods such as descriptive surveys and experiments in research. The research article’s findings show a positive trend toward improving educational practices in biology through the integration of STEM in PBL, with a growing body of literature focusing on this area. The findings of this study offer valuable insights for educators to improve students’ biology practical skills in higher education.